Status and prospect of workforce requirement for surgery in republic of Korea - Kim, Joo Hyun (The Korean Surgical Society, 2011)
PURPOSE: In order to prepare long-term alternatives to surgical residency training and workforce policies in Korea, objective data are needed; in addition, determination of the status of surgical procedures being performed is also needed. METHODS: Cases of surgeries performed by board-certified Korean surgeons for 1 year, from July 2009 to June 2010 were reviewed and analyzed. Variation of the last five years was also investigated against the number of surgery cases of the same item and for data on status of population, medical institutions, and surgeons. RESULTS: Difficulty in distribution of a given surgery varied according to the classification of medical institution types, and performance of highly difficult surgeries occurred more in tertiary hospitals. The number of surgeries has increased over the last 5 years (28.1%). The number of surgeries among elderly patients (41.5%), high difficulty (41.8%), and tertiary hospitals (34.9%) has especially increased. There has been no increase in the number of diagnosis related group claim cases for the last 5 years (-0.8%). 43.3% of surgeons working at private clinics in Korea did not present surgery as an indicating item of their clinics. CONCLUSION: While the demand for surgeons in high risk and highly difficult surgeries is continuously increasing, stagnation is expected in the traditional area. Considering the proportion and current status of surgeons working at private clinics, the need for a realistic reduction in the quota of surgical residents and reconsideration of personnel policies is raised.